Peace Education at Secondary School: a Learning Model in Aceh, Indonesia - Suadi Zainal; Saifuddin Yunus; Fadli Jalil (AIBPM Publisher, 2019)
Peace education is crucially needed in formal schools throughout Aceh to build peace culture among young generations, but Aceh government has not supported the peace education by a policy to establish peace education standard at secondary school. This study aims to examine the peace education has been tough at a secondary school in East Aceh. The research used a qualitative approach, which data was collected by depth interview and study of the document. The results show that peace education has been implemented in different ways at senior high schools in East Aceh. Some schools have tough it in a particular way, separated from the other subjects, and some schools others have tough it incorporative.